The Hirschfeld Archives Violence, Death, and Modern Queer Culture - Bauer, Heike (Sexuality Studies, 2017)
This work examines how death, suicide and violence shaped modern queer culture, arguing that negative experiences, as much as affirmative subculture formation, influenced the emergence of a collective sense of same-sex identity. Bauer looks for this history of violence in the work and reception of the influential sexologist Magnus Hirschfeld (1868-1935), and through Hirschfeld's work examines the form and collective impact of anti-queer violence in the first half of the twentieth century. Hirschfeld's archive (his library at the Institute for Sexual Sciences in Berlin) was destroyed by the Nazis in 1933, so the archive of Bauer's title is one that she's built from over a hundred published and unpublished books, articles, films and photographs.